2018
DOI: 10.1122/1.5049378
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the rheological properties of polypropylene under elongational flow by adding polyethylene

Abstract: Adding polyethylene greatly affects the rheological response of isotactic polypropylene (PP) under uniaxial elongational flow. Though strain hardening in the transient elongational viscosity barely appeared in pure PP, we induced strain hardening by adding low-density polyethylene (LDPE) to PP, even though the blends showed a phase-separated structure. During elongational flow, LDPE droplets dispersed in the PP were deformed in the flow direction. Because LDPE shows marked strain hardening in the elongational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The viscoelastic properties of PP‐H and PE‐L were reported previously. [ 27,28,36 ] For PS samples, the number‐ ( M n ) and weight‐average ( M w ) molecular weights, as evaluated by gel permeation chromatography (HLC‐8020, Tosoh, Japan), were M n = 99,000 and M w = 240,000 for PS‐H, and M n = 3300 and M w = 4000 for PS‐L. The viscoelastic properties for PS‐H and PS‐L were summarized in preceding papers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viscoelastic properties of PP‐H and PE‐L were reported previously. [ 27,28,36 ] For PS samples, the number‐ ( M n ) and weight‐average ( M w ) molecular weights, as evaluated by gel permeation chromatography (HLC‐8020, Tosoh, Japan), were M n = 99,000 and M w = 240,000 for PS‐H, and M n = 3300 and M w = 4000 for PS‐L. The viscoelastic properties for PS‐H and PS‐L were summarized in preceding papers.…”
Section: Methodsmentioning
confidence: 99%
“…This is currently one of the main purposes of employing polymer blends. Their purposes can roughly be classified into two categories: (1) to provide strain hardening in the transient elongational viscosity [ 23‐31 ] and (2) to decrease the shear viscosity to enhance flowability. In the latter case, adding low‐molecular‐weight compounds has been employed as a conventional method, which largely reduces the shear viscosity in the low shear rate region.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that the high aspect ratio fibrils change the rheological behavior of the matrix. [ 75, 87‐89 ] The polymer fibrils of a high aspect ratio form a physical network structure inside the polymer matrix and endow it with strain hardening behavior. Furthermore, the fibrils enhance the crystallization rate and increase the number of crystals of the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of rubbery materials to enhance the mechanical toughness is another major target for polymer blends. [1][2][3][4] Although various blend techniques have been proposed recently to improve the processability, [5][6][7][8][9][10][11] there is still a strong need to reduce the shear viscosity, especially for injection molding of engineering plastics.…”
Section: Introductionmentioning
confidence: 99%